Activity of the Special Commission to Fight Corrupt Practices and Activities Detrimental to Socialized Economy (based on materials of the Commission and its Warsaw Branch) (Archives of Criminology, 1996)
The Special Commission to Fight Corrupt Practices and Activities Detrimental to Socialized Economy operated in 1945-1954. Appointed by a decree of the the Council of Ministers in November 1945, it was to detect and prosecute offenses againts economic or social interests of state.As an institution of the machine of power of Polish stalinism, the Commision has not been studies extensively so far. Also fragmentary is the knowledge on its methods of operation on repression imposed. The sole source of such knowledge are preserved archival materials.The Special Commission operated through its subordinate branches which it appointed nationwide and in Polish diplomatic agencies abroad. Established as an extraordinary agency with special powers, it had very broad competencies and the certainty of cooperation on part of the criminal justice system. From 1950 on, it also took over a part of political cases. Although the range of offenses detected and prosecuted by the Commission had been relatively narrowly designed, the Commission’s actual competencies were very broad indeed. Members of the Special Commission were originally appointed by Presidium of the National People’s Council and then by the Council of State.The Commission’s regional agencies were its branches, submitted to its Executive Office until 1950 and then to its Chairman after the Office had been liquidated. The Branches were established in all of the then existing provinces, in four big industrial regions, and separately in the cities of Lodz and Warsaw. As the need arose, temporary branches were also formed in smaller regions.Obliged to execute the Branches’ decisions were all state and local offices, judicial authorities and prosecutor’s offices, as well as all control agencies. Members of the branches took the oath designed for judges and public prosecutors.The branches’ main task was to detect and prosecute economic offenses, including especially: appropriation and plunder of public property, corruption and bribery, profiteering, and looting of property abandoned through war events, that is actions detrimental to the interests of public life. According to the specific socio-economic nature of their individual spheres of operation, four types of branches emerged: those in the Regained Territories of Western Poland; branches operating in the main industrial regions; those in agricultural regions; and coastal branches whose work was made specific by thc existence of ports. Still another branch that can be distinguished here is the Warsaw one which dealt with the specific problems of the capital city and central offices.The Special Commission controlled its branches through briefings and, first of all, through distributed instructions. The branches were ordered to organize mass meetings with the local population, to promote their achievements in crime control, and to pursue preventive activities. The instructions stressed the need to cooperate with local social organizations and to stay in touch and cooperate with agencies of the Communist Party. Yet the agencies whose part in the work of the branches was the greatest were provincial prosecutor’s offices, courts, and the Civic Militia. The branches attaches great weight to the work of so-called Complaints Office which received both complaints and denunciations.Under the decree that established the Special Commission and a subsequent amendment of that act, cases prosecuted by the Commission were decided bv courts under the then valid law. A representative of the Commission or of its branch appeared as auxiliary prosecutor. In cases not referred to the court, the Commission had its own system of penalties to be imposed upon completion of the investigation. Imposed could be the following penalties: committal to a labor camp for up two years; forfeiture of property acquired through the offense and of objects used in its perpetration; temporary detention for 3 to 6 months; fine and other additional penalties. Until 1950, the branches could only impose fine for violation of the regulations on trade.In 1950, the system of penalties was extended, and so were the branches’ powers to impose those penalties. The accused persons were deprived of the right to be assisted by a defense counsel. Originally dealing with investigation and prosecution only, the Commission and its branches now became extrajudicial adjudicating agencies.In Decmber 1954, the Special Commission and its branches were abolished. Cases formerly examined by he Commission were handed over to courts. The problem of penalties imposed by the Special Commission and its branches was ultimately solved by the 1956 amnesty law which erased all of their decisions.The Warsaw Branch was established at a later date, that is in May 1946; apart from a brief period from 1948 till 1950, it covered Warsaw and the Warsaw province. Its specific feature was the two-sidedness of its work. On the one hand, it would examine local cases; on the other hand, being the Central Branch, it was competent with respect to the entire central state machine. Starting from 1950, the Warsaw Branch no longer conducted inquiries but only decided in cases prepared by the public prosecutor.The Warsaw Branch received information from state and local offices, private persons and social institutions, and also from other branches if the informajtion in question suggested the defendant’s or case’s connections with the central state offices.In the years 1946-1947, the Branch examined over 16 thousand cases – the biggest load of all branches - and this trend was to persist till the end of its operation. Prevailing among tle information received, in the years 1951 - 1952 in particular, were cases of profiteering. Examined most often were cases of illicit alcohol distilling, followed by malfeasance in office: corruption and bribery. In1953, the number of the latter increased twice as compared to the previous year. Among  cases examined by the Branch, there were also those of plunder and appropriation of public property, trade in golt and foreign currency, and forgery of tobacco monopoly products. There were also cases of economic sabotage at the workplace.As regards the way the Branch dealt with the cases it examined, convictions prevaild especially in the 1950s. The penalty imposed most often was fine. Also in this respect, the Warsaw Branch led among its other regional counterparts. The second most frequent penalty was committal to a labor camp. Forfeiture of property was imposed just as often.The Special Commission and its branches, the Warsaw Branch included, organized preventive campaigns and special operations. The former aimed at removing circumstances conducive to crime. They were directed against groups of persons causing damage to the economy. Both types of operations often resulted in detection of abuses. Special operations involved searches.From the beginning, the main task of the Special Commission and its branches was to be detection of and fight against offenses in the economic sphere. Restructuring of the economy towards the communist system was closely related to political struggle. From 1950 on, the Commission and its branches became tools of political terror. In labor camps, agencies of the Communist Party and security services would draw up political profiles of persons for economic offenses; many a time, the profile mattered more than the offense itself. The labor camps were advised to organize socio-political education for their inmates.The Commission and its branches treated corrupt practices in state-owned farms as acts of great political importance. Similar treatment was received by offenses committed by private owners of bigger farms.The range of political “offenses” examined by the Special Commission and its branches was very broad. Among them, two groups are most distinct. One of tchem included “offenses” resulting from anti-State activity, such as keeping materials containing “false information” about State, or propagation of “false” anti-State or anti-Communist information. The other group were “offenses” reflecting a person’s attitude to the USSR, as e.g. criticizing Stalin, insulting the effigies of Stalin and Rokossovski, doubts as to the identity of those guilty of the Katyn forest massacre, criticizing kolkhozes and the Polish-Soviet alliance.In the years 1950-1954, in Warsaw and the Warsaw province, 137 severe sentences were passed for anti-State “offenses” and for those reflecting a person’s attitude to the USSR. Prosecuting those “offenses”, the Commission and its Warsaw Branch often resorted to provocation and frequently took over cases in which the Security Office failed to gather sufficient evidence.In the years of operation of the Special Commission and its branches, a person could be punished for staying in touch with his family in the West, for corresponding with embassies of Western States, keeping forbidden books, being Jehovah;s Witness, and for anything that could be classed as hostile propaganda.The Special Commission to Fight Corrupt Practices and Activities Detrimental to Socialized Economy and its Warsaw Branch have made history. They are remember convicted by those agencies were granted pardon by President of the Republic of Poland or, later on, by the Council of State.Yet the activity of the Special Commission and its Warsaw Branch could not prevent the people’s growing discontent which eventually found vent in June 1956.